1986
DOI: 10.1136/bmj.293.6541.227
|View full text |Cite
|
Sign up to set email alerts
|

Angina pectoris-like pain provoked by intravenous adenosine in healthy volunteers.

Abstract: In a study to characterise the chest pain induced by adenosine this agent was given as a bolus into a peripheral vein to six healthy volunteers (five men) aged 30-44. On the first day the maximum tolerable dose was determined in each case. On the second day three doses of adenosine (one third, two thirds, and the full maximum tolerable dose) and three doses of saline were given single blind in randomised order. Thereafter aminophylline 5 mg/kg was given and the procedure repeated in a different randomised orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(63 citation statements)
references
References 11 publications
3
59
0
1
Order By: Relevance
“…Transient retrosternal chest pain was experienced by nine of the 10 patients, as previously described (Watt & Routledge, 1985;Sylven et al, 1986). This angina-like pain was shown in the present study to be associated with an increase in coronary flow.…”
Section: Discussionsupporting
confidence: 83%
“…Transient retrosternal chest pain was experienced by nine of the 10 patients, as previously described (Watt & Routledge, 1985;Sylven et al, 1986). This angina-like pain was shown in the present study to be associated with an increase in coronary flow.…”
Section: Discussionsupporting
confidence: 83%
“…If a chemical pain stimulus is involved, the substance that has been most recently linked to the production of angina-like chest pain is adenosine. Sylven et al 1 observed that an adenosine infusion resulted in chest pain even in patients without obstructive coronary artery disease. Subsequently, they gave varying amounts to healthy volunteers and caused dose-dependent chest pain in all of the volunteers.…”
Section: Pathophysiology Pain Studiesmentioning
confidence: 99%
“…30,31 Adenosine triphosphate and AM were effective in reversing the reductions in CBF, CI and int-PmO 2 induced by felypressin. Although ATP appears to have the advantage of allowing fine adjustments in dosage, it sometimes induces chest pain 32 and may be problematic for use in conscious patients. Amrinone appears to provide the favourable combination of cardiotonic effect, reduction of myocardial oxygen demand and increase in oxygen supply.…”
Section: Discussionmentioning
confidence: 99%